2012
DOI: 10.1007/s11240-012-0172-3
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and Agrobacterium-mediated transformation of multiple lily cultivars

Abstract: To pursue genetic improvement of lily, efficiency of both regeneration and transformation from callus cultures induced from different explants were evaluated in multiple cultivars. Thirty-five callus lines induced from filaments or styles and one control callus line derived from bulb scales of in total twenty lily cultivars representing Lilium longiflorum, Oriental 9 Trumpet and Longiflorum 9 Asiatic hybrids were maintained on a medium with 8.3 lM picloram (PIC). In this study, they were tested for their regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
1
15
0
2
Order By: Relevance
“…In most lily hybrids, the explants used for embryogenic callus induction have usually been taken from floral organs, bulb scales (Hoshi et al 2004;Wang et al 2012), leaves and seeds . We are aware of no research in Lilium species that has been done on stem axis explants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most lily hybrids, the explants used for embryogenic callus induction have usually been taken from floral organs, bulb scales (Hoshi et al 2004;Wang et al 2012), leaves and seeds . We are aware of no research in Lilium species that has been done on stem axis explants.…”
Section: Discussionmentioning
confidence: 99%
“…For successful production of genetically modified lily plants, one prerequisite is the establishment of a transformation protocol based on the regeneration and transformation competence of cells (Wang et al 2012). Plant cell suspensions are becoming the favored model system for this due to their properties of straightforward transformation, rapid cell proliferation and good growth characteristics (Santos-Ballardo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the transformation efficiency of ornamental lilies is quite low making it very laborious to generate a population of transgenic plants, and this may be one reason why only a few transformation studies have used lilies. Wang et al (2012) compared the Agrobacterium-mediated transformation efficiencies of eight ornamental lily cultivars, and the highest was 1.4 % for callus regenerated from filaments of the cultivar 'Santander'. Azadi et al (2010Azadi et al ( , 2011 found a low 0.5 % transformation efficiency but were able to engineer expression of seven carotenoid genes.…”
Section: Introductionmentioning
confidence: 99%
“…Structure of the T-DNA region of pCAMBIA3301:AtSIZ vector provided by Genomine INC (Pohang, Korea) (NPTII (neomycin phosphotransferase); NOS: nopaline synthase promoter; TNOS: 3' signal of nopaline synthase; 35S: Cauliflower Mosaic Virus (CaMV) 35S promoter 수행되어왔다 (Mercuri et al 2003;Nam and Kim 2004;Hoshi et al 2004;Ogaki et al 2008;Azadi et al 2010;Liu et al 2011;Wang et al 2012). 한편 유전자총을 이용한 형질전환 나리식물체 개발에 관한 연구에서는 1998년 최초로 Watad et al (1998) (Hoshino et al 2008;Kim et al 2007;Lin et al 2000), 히야신스 (Popowich et al 2007), 심비디움 (Roh et al 2011 and2013), 팔레놉시스 (Roh et al 2014)나 튤립 (Wilmink et al 1992) 등과 비교하면 형질전환연 구가 비교적 많이 수행되었음을 알 수 있다.…”
unclassified